2013
DOI: 10.1148/radiol.13121782
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Biopsy: RNA Isolation with Expression Profiling in Men with Metastatic Castration-resistant Prostate Cancer—Factors Affecting Diagnostic Success

Abstract: In men with mCRPC, percutaneous sampling of osseous metastases for genomic profiling is possible, but use of zoledronic acid for more than 1 year may reduce the yield of adequate tissue for RNA isolation. Sampling large low-attenuating lesions at their periphery maximizes yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 30 publications
4
26
1
Order By: Relevance
“…Based on prior studies, we predicted that sclerotic lesions would result in lower yield. (8, 11-14) Though we did not show a statistically significant correlation between attenuation and tumor yield, likely related to the small sample size of this cohort, lesions with greater attenuation (>400 HU) did have decreased PPC. In a retrospective analysis of 410 CT-guided biopsies of osseous lesions, imaging appearance was associated with biopsy accuracy (accuracy for sclerotic, lytic, or mixed lytic-sclerotic was 76%, 93%, and 92%, respectively).…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Based on prior studies, we predicted that sclerotic lesions would result in lower yield. (8, 11-14) Though we did not show a statistically significant correlation between attenuation and tumor yield, likely related to the small sample size of this cohort, lesions with greater attenuation (>400 HU) did have decreased PPC. In a retrospective analysis of 410 CT-guided biopsies of osseous lesions, imaging appearance was associated with biopsy accuracy (accuracy for sclerotic, lytic, or mixed lytic-sclerotic was 76%, 93%, and 92%, respectively).…”
Section: Discussioncontrasting
confidence: 67%
“…A previous study demonstrated that peripheral lesion sampling may be associated with increased yield (78% versus 52% for peripheral versus central sampling, p=0.24). (8)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technological advances in the processing of tissue from bone biopsies has enabled the performance as a valid approach for tissue acquisition from these patients 14 . Moreover, DNA and RNA sequencing from bone biopsy specimens is now technically feasible 15 . Such biopsies are being increasingly undertaken and even mandated in clinical trials.…”
Section: Introductionmentioning
confidence: 99%